تأثير موعد الإصابة بفيروس واي البطاطا في بعض المركبات الكيميائية, لأوراق التبغ الجافة, لصنفي التبغ برلي ( Br21), وفيرجينيا (Vk51), في الساحل السوري (Latakia University Journal -Biological Sciences Series, 2019)
هدف البحث دراسة تأثير الإعداء الميكانيكي, بفيروس واي البطاطا, في موعدين مختلفين, في التركيب الكيميائي, لصنفي التبغ, فيرجينيا (Vk51) , وبرلي .(Br21) أظهرت نتائج التحليل الكيميائي: 1)          تدهوراً في نوعية الأوراق المجففة للصنفين المدروسين, في معاملتي الإعداء بالفيروس, مقارنةً بالشاهد, وكان الإعداء الأول (الإصابة المُبكّرة) بالفيروس أكثر تأثيراً في المركبات ذات الخصائص النوعية في ورقة التبغ المُجففة من الإعداء الثاني (الإصابة المُتأخرة). 2)                         اختلافـاً في قيم بعض المركبات الكيميائية في المعاملة الواحدة، باختلاف موقع الأوراق على ساق النبات. The aim of this research was to study the effect of mechanical inoculation with potato virus Y (PVY) on chemical composition of tobacco cured leaves (varieties Virginia Vk51 and Burley Br21) correlated with tobacco quality. The results of chemical analysis of constituents of tobacco leaves showed the following: 1)          A significant deterioration of the quality of cured leaves of both early and late PVY infected varieties in comparison with healthy controls, and the early infection has led to drastic effect on chemical composition of cured leaves in comparison with late infection. 2)          Leaves position on the main stem has led to variation among some chemical composition of cured leaves in the same treatment.